Studies on the technical courses curricula in agriculture: time for a change? Estudos sobre os currículos dos cursos técnicos em agropecuária: momentos de mudanças? - Altoé, Dayane Silva Santos; de Souza, Paulo Marcelo; Martínez, Silvia Alicia (Programa de Pós-graduação em Desenvolvimento, Agricultura e Sociedade da Universidade Federal Rural do Rio de Janeiro (CPDA/UFRRJ), 2018)
This work deals with the knowledge produced in the field of Professional Agricultural education. In light of the concept of curriculum prepared by Silva (2003), this paper presents and discusses the most recurrent themes among the studies involving the curricula of technical courses at the high school level in agriculture offered by the Federal Network of Vocational Education, Science and Technology between the years 2005-2012. On the methodological aspects, this work was restricted to academic research at the graduate level provided by the Brazilian Digital Library of Theses and Dissertations as well as the works presented in the four editions of the National Seminar of Vocational and Technological Education. Among the considerations was possible to identify two predominant themes among these studies: the consequences of the reform of vocational education promoted by Decree 2.208/97 and its replacement by Decree 5.154/04 and finally, the introduction of environmental education in the curriculum of technical courses at the high school level in agriculture.Keywords: curriculum; agricultural vocational education; environmental education.ALTOÉ, Dayane Silva Santos; SOUZA, Paulo Marcelo de; MARTÍNEZ, Silvia Alicia. Estudos sobre os currículos dos cursos técnicos em agropecuária: momentos de mudanças? Estudos Sociedade e Agricultura, v. 26, n. 3, p. 681-700, out. 2018. Submitted in february 2018.Accepted in august 2018.